2017
DOI: 10.1016/j.hpb.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of combined preoperative prognostic nutritional index and body mass index in HCC after hepatectomy

Abstract: preoperative PNI/BMI is an independent predictor of outcome for HCC patients, especially in patients with early stage HCC. Intriguingly, the PNI + BMI combination can enhance the accuracy of prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 25 publications
(42 reference statements)
6
45
2
Order By: Relevance
“…Several studies have reported that a low BMI (underweight) correlates significantly with low albumin levels and sarcopenia, which are clinical manifestations of malnutrition and poor immune function. Ji and co‐workers indicated that a low BMI reflected a poor nutritional status, typically accompanied by a low lymphocyte count suggesting immunological suppression. All of these findings can explain why underweight patients may have a poor postoperative prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that a low BMI (underweight) correlates significantly with low albumin levels and sarcopenia, which are clinical manifestations of malnutrition and poor immune function. Ji and co‐workers indicated that a low BMI reflected a poor nutritional status, typically accompanied by a low lymphocyte count suggesting immunological suppression. All of these findings can explain why underweight patients may have a poor postoperative prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, immuno-nutritional status has been reported to be associated with outcomes in patients with HCC [12][13][14]. The controlling nutritional status (CONUT) score has been developed as an objective assessment tool of nutritional status [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, some previous studies indicated that BMI and GPS could not be appropriate prognostic factors for HCC patients [5,6]. Noteworthily, indictors correlated with malnutrition and inflammation have been proven to be a reliable prognostic factors [7][8][9][10][11][12]. Nutritional status plays an important role on patients recovery from hepatectomy [13].…”
Section: Introductionmentioning
confidence: 99%